Effect of Processing Method on the Quality of Palm Kernel Cake: Chemical Composition and Nutrient Utilization in Enzyme Supplemented Diets - Boateng, M; Okai, D B; Baah, J; Donkoh, A (ANIMAL PRODUCTION, 2013)
Abstract. The feed value of palm kernel cake (PKC) from two expeller sites and two hydrothermal production facilities were assessed using 30 laboratory rats as a model. Following chemical analysis, the PKC were incorporated at 0% (control, CON) or 35% (w/w) into isonitrogenous maize-based diets (2.9% N, DM basis) and fed to individually caged albino rats for 28 day. All PKC diets included 0.5% (w/w) Alzyme Vegpro (Alltech Canada, Guelph, ON). PKC from expellers (E1, E2) contained more  fatty acids (FA) and less crude protein (CP) than did PKC from hydrothermal production (H1, H2), averaging 15.8% vs 7.7% FA and 13.3% vs. 19.7% CP (DM basis), respectively. Lauric, oleic, myristic and palmitic acids were predominant in PKC, accounting for 84% of total FA. E1 and E2 had higher essential amino acid contents (average 67.1% of total AA) than did H1 or H2 (average 64.1%). Gain and feed efficiency (FE; feed/gain) were similar between rats fed E1 or E2 diets and those fed CON (2.1 and 2.2 g/d vs. 2.2 g/d; 4.7 and 4.3 g/d vs. 5.3, respectively), but were reduced in rats fed H1 or H2 diets (1.5 and 1.3 g/d gain; 7.1 and 7.0 FE) compared with CON. This study indicated that expeller-produced PKC could potentially be included in maize-based starter diets for pigs at up to 35% with no adverse effects on growth. Key words: Amino acid, fatty acid, expeller, hydrothermal Abstrak. Nilai pakan PKC dari dua expeller dan dua fasilitas produksi hidrotermal diukur menggunakan 30 mencit sebagai model. PKC dianalisa secara kimiawi dengan kadar 0% (kontrol, CON) atau 355 (w/w) ke dalam pakan berbahan dasar jagung isonitrogen (2.9% N, BK) dan diberikan kepada mencit albino yang dikandangkan secara individu selama 28 hari. Semua pakan PKC mencakup 0.5%(w/w) Alzyme Vegpro (Alltech Canada, Guelph, ON). PKC expeller (E1, E2) mengandung lebih banyak asam lemak (FA) dan lebih sedikit protein kasar (PK) daripada PKC dari produksi hidrotermal (H1, H2), dengan kisaran 15,8% vs 7,7% FA dan 13,3% vs 19,7% PK (berdasarkan BK). Asam laurat, oleat, miristat dan palmitat mendominasi PKC, mencakup 845 dari total asam lemak. E1 dan E2 mempunyai kandungan asam amino esensial (rata-rata 67,1 dari total asam amino) daripada H1 dan H2 (rata-rata 64,1%). Efisiensi pakan dan pertumbuhan (FE; pakan/bijian) sama antara tikus yang diberi pakan E1 atau E2 dengan yang diberi CON (2,1 dan 2,2 g/hari vs. 2,2 g/hari; 4,7 dan 4,3 g/hari vs. 5,3), namun berkurang pada tikus yang diberi pakan H1 atau H2 (1,5 and 1,3 g/hari; 7,1 dan 7,0 FE) dibandingkan dengan CON. Penelitian ini menunjukkan bahwa PKC expeller berpotensi disertakan dalam pakan berbahan dasar jagung untuk babi hingga kadar 35% tanpa berpengaruh buruk terhadap pertumbuhan. Kata kunci: Asam amino, asam lemak, expeller, hidrotermal